Unmasked - Lloyd Webber, Andrew 1948- (Harper, an imprint of HarperCollinsPublishers, 2018)
Andrew Lloyd Webber dominated musical theater in the 1970s and 80s. His hit shows included Jesus Christ Superstar, Evita, Cats, The Phantom of the Opera, and most recently, School of Rock. Now the composer takes stock of his achievements, the twists of fate and circumstance that brought him both success and disappointment, and the passions that inspire and sustain him. The son of a music professor and a piano teacher, Lloyd Webber reveals his artistic influences, from his idols Rodgers and Hammerstein and the perfection of South Pacific's "Some Enchanted Evening," to the pop and rock music of the 1960s and Puccini's Tosca, to P.G. Wodehouse and T.S. Eliot. Taking us behind the scenes of his productions, he reveals fascinating details about each show, including the rich cast of characters involved with making them, and the creative and logistical challenges and artistic political battles that ensued. Lloyd Webber shares his recollections of the works that have become cultural touchstones: writings songs for a school production that would become his first hit, Joseph and the Amazing Technicolor Dreamcoat; finding the coterie of performers for his classic rock opera Jesus Christ Superstar; developing his first megahit, Evita, which would win seven Tonys Awards, including Best Musical; staking his reputation and fortune on the groundbreaking Cats; and making history with the dazzling The Phantom of the Opera
Includes index
Keywords: Lloyd Webber, Andrew -- 1948-; Lloyd Webber, Andrew / 1948-; Lloyd Webber, Andrew / 1948- / Cats; Lloyd Webber, Andrew / 1948- / Jesus Christ superstar; Lloyd Webber, Andrew / 1948- / Phantom of the Opera; Cats (Lloyd Webber, Andrew); Jesus Christ superstar (Lloyd Webber, Andrew); Phantom of the Opera (Lloyd Webber, Andrew); Musical theater / Biography; Musical theater / Anecdotes; Musical theater / History and criticism / 20th century; Musicals / Writing and publishing / Anecdotes; Composers / England / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Music; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; MUSIC / Individual Composer & Musician; Composers; Musical theater; Musicals / Writing and publishing; England; Musicals / History and criticism; 1900-1999; Anecdotes; Autobiographies; Biography; Criticism, interpretation, etc; Autobiografie